Maintaining Research Integrity While Balancing Cultural Sensitivity: A Case Study and Lessons From the Field. Issue 1 (11th September 2015) - Sibbald, Rebekah; Loiseau, Bethina; Darren, Benedict; Raman, Salem A.; Dimaras, Helen; Loh, Lawrence C.
Abstract: Contemporary emphasis on creating culturally relevant and context specific knowledge increasingly drives researchers to conduct their work in settings outside their home country. This often requires researchers to build relationships with various stakeholders who may have a vested interest in the research. This case study examines the tension between relationship development with stakeholders and maintaining study integrity, in the context of potential harms, data credibility and cultural sensitivity. We describe an ethical breach in the conduct of global health research by a arising from the ad‐hoc participation of a community stakeholder external to the visiting research group. A framework for reflection is developed from a careful examination of underlying factors and presented with a discussion of consequences and mitigation measures. This framework aims to present lessons learned for researchers working abroad who might face similar situations in their work.